PENGARUH PENERAPAN METODE EKSPERIMEN PADA MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS XI MERDEKA SMAS PPM Al-IKHLASH LAMPOKO - Rahbin, Salsabila; Herawati, Netti; Husain, Halimah (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to determine whether there is an influence of the experimental method on the Discovery Learning model on the Science Process Skills of class XI Merdeka students of SMAS PPM Al-Ikhlash Lampoko. The method used is a quasi-experimental method with a posttest only control group design. The population consists of all class XI students who study chemistry at SMAS PPM Al-Iklash Lampoko which consists of two classes using the selected simple random sampling technique, class XI Merdeka 1 as the experimental group that learns using the experimental method on the Discovery learning model and class XI Merdeka 2 as the control group that learns using the Discovery learning model. Descriptive statistical analysis on the science process skills test obtained an average in the experimental class of 78.7 and a control class of 56.4. The results of the inferential statistical test obtained Uhitung = 48 and Ukritik value = 127. Because Uhitung ≤ Ukritik (48 <127) then H1 is accepted and H0 is rejected. Based on the calculation results obtained, it can be concluded that there is an influence of the application of experimental methods in the discovery learning model on the science process skills of class XI Merdeka Students of SMAS PPM Al-Ikhlash Lampoko (Acid Base Material).